The Urgency of Tari Mabuk in Bedendang Ceremony - Afni Rachmawati (Postgraduate School, Universitas Negeri Padang, 2019)
This article was purposed to explain about the urgency of a Tari Mabuk that has a function of binding in the bedendang ceremony as a traditional ceremony of Bengkulu community. This article was a part of the study finding on Tari Mabuk in bedendang ceremony in Bengkulu; this research was conducted by using qualitative approach that had descriptive characteristic. Data was obtained through interviews, observation, and documentation. Data analysis techniques were processed with three Miles and Huberman models. Study findings indicated that Tari Mabuk is a sacred traditional dance that became the most important part in the implementation of bedendang ritual in Bengkulu where Tari Mabuk serves as the main part in bedendang ceremony. The meaning was legitimacy of bedendang ceremony implementation was associated with the existence of Tari Mabuk. If Tari Mabuk was not performed in ceremony, the ceremony couldn’t be continued. Keywords: Tari Mabuk in bedendang ceremony.